(Invited) Understanding and Controlling Chemo-Mechanical Coupling in Perovskite Oxides. (28th July 2016) - Perry, Nicola H.; Marrocchelli, Dario; Bishop, Sean R.; Tuller, Harry L.
Abstract : Mixed ionic and electronic conducting perovskites that can readily exchange oxygen with the atmosphere exhibit a chemo-mechanical coupling between their oxygen content and their lattice dimensions. The lattice dilation accompanying oxygen loss, termed "chemical expansion, " causes large chemical stresses in devices during operation that can lead to mechanical failure. This paper describes our work aimed at understanding, across multiple length scales, which factors impact chemical expansion coefficients in perovskites. Polycrystalline gallate and titanate perovskites containing multivalent Ni, Fe, and Co have been studied using in situ thermogravimetry, dilatometry, and diffraction to probe the chemical expansion process at macroscopic and crystal structure levels. Density functional theory, molecular dynamics, and empirical simulations have provided atomistic insight into changes taking place on the anion and cation sublattices during oxygen loss. Factors impacting the magnitude of the chemo-mechanical coupling, including oxygen vacancy radii, charge localization on cations, temperature, and crystal symmetry have been identified.